Lonidamine liposomes to enhance photodynamic and photothermal therapy of hepatocellular carcinoma by inhibiting glycolysis - Lei Lei; Wenbin Dai; Jiaping Man; Haitao Hu; Qiao Jin; Bo Zhang; Zhe Tang (Journal of Nanobiotechnology, 2023)
Abstract Phototherapy, including photodynamic therapy (PDT) and photothermal therapy (PTT), has great promise in the treatment of cancer. However, there are many obstacles that can restrict the therapeutic efficacy of phototherapy. The hypoxic tumor microenvironment can restrict the production of reactive oxygen species (ROS) in PDT. As for PTT, the thermotolerance of cancer cells may lead to ineffective PTT. In this study, IR780 and glycolysis inhibitor lonidamine (LND)-encapsulated liposomes are prepared for photodynamic and photothermal therapy of hepatocellular carcinoma. IR780 can be used as a photosensitizer and photothermal agent for simultaneous PDT and PTT after being irradiated with 808 nm laser. LND can reduce the oxygen consumption of cancer cells by inhibiting glycolysis, which will relieve tumor hypoxia and produce more ROS for PDT. On the other hand, energy supply can be blocked by LND-induced glycolysis inhibition, which will inhibit the production of heat shock proteins (HSPs), reduce the thermotolerance of tumor cells, and finally enhance the therapeutic efficacy of PTT. The enhanced PTT is studied by measuring intracellular HSPs, ATP level, and mitochondrial membrane potential. The antitumor effect of IR780 and LND co-loaded liposomes is extensively investigated by in vitro and in vivo experiments. This research provides an innovative strategy to simultaneously enhance the therapeutic efficacy of PDT and PTT by inhibiting glycolysis, which is promising for future creative approaches to cancer phototherapy.